Evaluation of Lantana camara Leaf Extract as Biopesticide for Lifecycle Disruption in Spodoptera litura - Mallarangeng, Rahayu; Syamsinar; Hasan, Asmar; Hisein, Waode Siti Anima; Taufik, Muhammad; Nuriadi; Johan, Eko Aprianto (Bogor Agricultural University, Indonesia, 2025)
Spodoptera litura is a destructive agricultural pest whose management is hindered by synthetic pesticides' ecological and health risks. Plant-based biopesticides, such as Lantana camara leaf extract, provide a sustainable alternative due to the presence of bioactive phytochemicals with pesticidal properties. Therefore, this study aimed to evaluate the efficacy of L. camara extract in disrupting the lifecycle of S. litura. A completely randomized design was adopted, and six treatment concentrations of L. camara extract, namely 0%, 6.25%, 12.5%, 25%, 50%, and 100%, were applied to second-instar larvae. Observations included larval development time, leaf consumption, pupation rate, pupal weight, moth emergence, and fecundity. Data were analyzed using ANOVA, and the result showed that the extract had strong dose-dependent effects on all variables. Pupation, moth development, and fecundity were inhibited by concentrations greater than 25%. Feeding activity was significantly reduced at higher concentrations, with a 100% concentration achieving a 3.67% leaf consumption rate after 48 hours. Larval development was delayed or halted entirely at critical thresholds. In conclusion, L. camara extract effectively disrupted the lifecycle of S. litura, providing immediate suppression and long-term population control. The dual-action potential, biodegradability, and natural origin made extract a sustainable alternative to synthetic pesticides. Future studies are recommended to validate these results under field conditions and evaluate impacts on non-target species.